(untitled) (Research, Society and Development, 2022)
In Brazil, the use of medicinal plants in the treatment of illnesses is influenced by indigenous, African and European cultures. Approximately 80% of the world population uses plants or their preparations in health care, making it a complementary therapy. Thus, the objective was to identify the indication made by doctors working in the Family Health Strategy for medicinal plants and/or herbal medicines. Thirty-one doctors from the Basic Health Units located in Juazeiro do Norte-CE were interviewed, using semi-structured forms. For data analysis, the Microsoft Excel 2010 program was used. 23 plant species indicated for medicinal purposes and 19 phytotherapeutic purposes were identified, and Cymbopogon citratus (DC.) Stapf, Matricaria chamomilla L., Aloe vera L. Burm.f. and Peumus boldus Molina were more representative among plants, and Valeriane® (Valeriana officinalis L.); Calman® (Passiflora incarnata L., Crataegus oxyacantha L. and Salix alba L.); Ginkgo biloba® Extract (Ginkgo biloba L.); Sintocalmy® (Passiflora incarnata L.) and Liberaflux® (Hedera helix L.) were the most representative among herbal medicines. It was found that doctors recommend plants and/or herbal medicines in the treatment of certain diseases, however further study is needed regarding their use and dosage.